A non‐electrolyte haemolysis assay for diagnosis and prognosis of sickle cell disease. (4th February 2013) - Milligan, C.; Rees, D. C.; Ellory, J. C.; Osei, A.; Browning, J. A.; Hannemann, A.; Gibson, J. S.
Key points: Red blood cells (RBCs) from the two main genotypes of sickle cell disease (SCD) patients showed haemolysis in deoxygenated isosmotic sucrose solution, to a greater extent than those from sickle trait individuals (HbAS). RBCs from normal individuals (HbAA) did not lyse. Several treatments reduced haemolysis in RBCs from HbSS patients – cytochalasin B, aromatic aldehydes ( o ‐vanillin and 5‐hydroxymethylfurfural), urea, low temperature and high pH. These effects were not due to increased oxygen affinity of haemoglobin. Long‐term treatment of patients with hydroxyurea was also associated with reduced levels of haemolysis. Treatment with aromatic aldehydes and urea reduced sickling of HbSS RBCs in deoxygenated saline solutions. Further, RBCs from sickle trait individuals (HbAS) could be induced to sickle under acidic (pH 6), hypertonic (400 mosmol kg −1 ) conditions. When these conditions were reproduced in sucrose solutions, HbAS RBCs also showed considerable haemolysis. Results suggest that haemolysis of HbS‐containing RBCs is associated with HbS polymerisation, perhaps damaging the RBC membrane. These findings suggest that haemolysis may be used as a simple, novel technique to diagnose SCD, using the altered membrane permeability of RBCs rather than the presence of HbS per se . As extent of haemolysis varies between individuals and is reduced following hydroxyurea treatment, the method may also be useful prognostically. Abstract Red blood cells (RBCs) from patients with sickle cell disease (SCD) lyse in deoxygenated isosmotic non‐electrolyte solutions. Haemolysis has features which suggest that it is linked to activation of the pathway termed Psickle . This pathway is usually described as a non‐specific cationic conductance activated by deoxygenation, HbS polymerisation and RBC sickling. The current work addresses the hypothesis that this haemolysis will provide a novel diagnostic and prognostic test for SCD, dependent on the altered properties of the RBC membrane resulting from HbS polymerisation. A simple test represented by this haemolysis assay would be useful especially in less affluent deprived areas of the world where SCD is most prevalent. RBCs from HbSS and most HbSC individuals showed progressive lysis in deoxygenated isosmotic sucrose solution at pH 7.4 to a level greater than that observed with RBCs from HbAS or HbAA individuals. Cytochalasin B prevented haemolysis. Haemolysis was temperature‐ and pH‐dependent. It required near physiological temperatures to occur in deoxygenated sucrose solutions at pH 7.4. At pH 6, haemolysis occurred even in oxygenated samples. Haemolysis was reduced in patients on long‐term (>5 months) hydroxyurea treatment. Several manoeuvres which stabilise soluble HbS (aromatic aldehydes o ‐vanillin or 5‐hydroxymethyl, and urea) reduced haemolysis, an effect not due to increased oxygen affinity. Conditions designed to elicit HbS polymerisation in cells from sickle trait patients (deoxygenated hyperosmotic sucrose solutions at pH 6) supported their haemolysis. These findings are consistent with haemolysis requiring HbS polymerisation and support the hypothesis that this may be used as a test for SCD.